Biochemical analysis of preliminary clusters in the non-lineage panel - Naessens, Jan; Nthale, J.M.; Muiya, P. (Elsevier, 1996)
After the preliminary clustering of the whole workshop panel using flowcytometry data, we selected those clusters that were composed of mAbs that bound a broad range of cells. To obtain evidence that mAbs in each of these preliminary clusters detected the same antigen, they were tested for their capacity to compete with each other for binding to a target cell and the molecular weights of their antigens were estimated after immunoprecipitation. Most preliminary clusters in the non-lineage panel contained control mAbs that had been characterised in one of the previous workshops, and this study therefore increased the number of mAbs available to each of these non-lineage antigens. One new interesting cluster, BoWC14, was described which defined an antigen on myeloid cells and a subpopulation of CD4, CD8 and WC1 T lymphocytes (BT3/8.12 and IL-A155). An additional cluster, which did not fit into any other panel, contained mAbs specific for an antigen restricted to the erythroid lineage and received the nomenclature BoWC15 (ANA8, IL-A135, IL-A137, IL-A138 and IL-A160).